A study on Training Requirements of Pharmaceutical Sales representatives with Special Reference to Erode District - Sadika Sultana, M.; Manivannan, Dr. L.; Mohan K. Pillai, Dr. (Journal of Contemporary Research in Management (JCRM), 2013)
Indian pharmaceutical industry is encountering several challenges in the current scenario of economic downturn. The study was carried out to understand the training requirements of Pharmaceutical Sales Representative that can augment them to meet the competitive drug market, and to withstand the competition from MNC’s and other global players from abroad. Previous studies have revealed that preference of MNC drugs over Indian company drugs and a well trained Pharmaceutical Sales representative is very helpful in such a scenario. The study arrived at divulging the current methods and goes on to suggest the changes or improvements that need to be made in order to face the challenges from abroad. The study was done on 410 Pharmaceutical sales Representatives from erode district, and it was found that there is a need to improve the same. Tools like chi- square test, percentage analysis and Garrett Ranking Test were carried out to gain an insight on the opinion of the Pharmaceutical Sales Representatives. The study revealed that stress relief training and increasing the duration of the training were ranked at the first and second position as far as areas where training is required.